THE EFFECT OF WATER HYACINTH (Eichornia crassipes) FROM POLLUTED WATER IN THE RATION AND ITS IMPACT ON THE PERFORMANCE OF LANDRACE PIGS - Sudiastra, I W.; Mahardika, I G.; Dharmawan, I N.S.; Budaarsa, K. (E-Journal of Animal Science Udayana University, 2015)
The use of waste as component material ration provides benefits that do not compete with humans, is relatively inexpensive and can reduce environmental pollution. The purpose of this study were to determine the benefits and the impact of the provision of water hyacinth ( Eichornia crassipes ) from polluted waters as feed suplement on the performance of Landrace pigs. This research used completely randomized design (CRD) with 4 treatments and 4 replications. A total of 16 Landrace pigs with an average live weight of 20 kg were used in this study. The four treatments are: (A) pigs received rations without water hyacinth, (B) pigs received rations plus 2.5% water hyacinth, (C) pigs received rations 5% plus water hyacinth and (D) pigs received rations 7.5% water hyacinth plus. Growth of pigs, feed intake, feed efficiency, feed digestibility and nutrient digestibility, carcass composition and quality, fat content, and the content of heavy metals (Pb and Cd) in the meat, intestines, kidneys and liver were evaluated in this study.  The results showed that the use of water hyacinth from polluted waters up 7.5% in the feed had no effect on the growth of pigs (P> 0.05). They tends to improve feed intake and consumption of organic matter, as well as  increasing their feed conversion but the difference significant (P> 0.05). Digestibility of dry matter, organic matter and nutrient but were not significantly different by tend to decrease with the increasing the use of water hyacinth originated from polluted waters in the ration  (P> 0.05).  Digestibility of dry matter, organic matter digestibility and nutrient digestibility  were also tend to decrease by  increasing the use of water hyacinth originated from polluted waters in the ration but not significantly different (P> 0.05). The use of water hyacinth up to   7.5%  in the ration did not affect to the percentage and pieces of carcass weight (P> 0.05). The content of heavy metals (Pb and Cd) in meat, kidney, liver and small intestine of pigs received rations containing water hyacinth originated from polluted water, still below the limit of safe consumption.  It was concended tha the use of water hyacinth from polluted waters as pig feed material to the level of 7.5% did not significantly affect the performanceof Landrace pig in tern of growth carcass weight, carcass percentage and meat quality